The Effect of Chimney Height Variation on the Performance of a Solar-Powered Cascara Coffee Dryer Prototype - Faisal Faisal; Suryadi Suryadi; Irhamna Ikhwan; Muhammad Sayuthi; M. Iqbal Adhya Putra (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to evaluate the effect of chimney height variation on the performance of a solar-powered cascara coffee dryer prototype. Chimney height is an important parameter in drying systems because it affects the rate of hot air flow, relative humidity, and drying process efficiency. An experimental study was conducted by varying the chimney height in the dryer's air outlet duct, then observing the drying performance of coffee cherry husks (cascara) as the test material. The main parameters analyzed included drying time, temperature stability in the drying chamber, drying efficiency, and final product quality. The results showed that variations in chimney height had a significant effect on system performance. A chimney with a height of 220 cm proved to produce the best performance with a more stable air flow rate, consistent drying temperature, and 100% efficiency. This results in a faster, more even, and higher quality cascara drying process. The final product, dried cascara coffee, can then be processed into high-value herbal tea drinks and has the potential to increase coffee product diversification. Thus, this study confirms that proper chimney height adjustment is a crucial factor in the design and development of solar drying technology, especially for agricultural products such as coffee cherry skin. These findings are expected to serve as the basis for developing more efficient, environmentally friendly dryer designs that support increased added value for coffee derivative products at both the farmer and small-to-medium industry levels.